Primary Peritoneal Psammocarcinoma Misdiagnosed as an Heterotopic Ossification: A Case Report - Gayoung Jeon; Seo Young Park (Journal of the Korean Society of Radiology, 2023)
Primary peritoneal psammocarcinoma is a rare type of serous carcinoma that is characterized by the massive formation of psammoma bodies and the invasion of adjacent organs. A 55-year-old female who previously underwent a hysterectomy presented to the emergency room with severe abdominal pain. Contrast-enhanced CT revealed an intra-abdominal calcific mass. Initially, it was thought to be a heterotopic ossification due to the previous pelvic surgery with intact ovaries. However, this was diagnosed as a primary peritoneal psammocarcinoma. Primary peritoneal psammocarcinoma is a very rare disease entity that should be considered a differential diagnosis in patients with normal ovaries, massive ossification in the pelvic cavity, and calcific peritoneal nodules.